CLASSIFICATION OF POPULATION STRUCTURE FOR ALLELOPATHIC PROPERTIES IN ITCHGRASS (Rottboellia cochinchinensis) - Bundit, Apirat; Auvuchanon, Anyamanee; Pornprom, Tosapon (Faculty of Agriculture University of Brawijaya and Indonesian Agronomic Assossiation, 2014)
Biodiversity of Rottboellia cochinchinensis from different areas were studied by morphological traits and amplified fragment length polymorphism (AFLP) analysis for classify of an allelopathic ability. The correlation of the similarity/distance between AFLP markers (Jaccard coefficient) and morphological traits (Euclidean distance) was significant with r = â 0.84**. Itchgrass could be divided into two groups from both UPGMA and STRUCTURE analyses: the group A consisted of itchgrass from Chaehom-Lampang, Si Thep-Phetchabun, Phrom Phiram-Phitsanulok, Amphur Muang-Nakhon Sawan, Kamalasai-Kalasin, Amphur Muang-Chachoengsao and Bang Yai-Nonthaburi, whereas itchgrass from Amphur Muang-Chiang Mai, Pak Chong-Nakhon Ratchasima and Kamphaeng Saen-Nakhon Pathom constituted the group B. Allelopathic properties of itchgrass as representative from different group were determined in bioassay test, the result showed that the aqueous extract of itchgrass from Chaehom-Lampang area has a strong allelopathic ability on growth of Echinochloa crus-galli L., Bidens pilosa L. and Lactuca sativa L. than the other group. The molecular analysis was strongly supported in morphological analysis clustering with bioassay test for allelopathic ability, specific morphological traits were soft trichomes, and the dark purple stems and roots which can be used for the preliminary classification of allelopathic ability. Our findings suggest that classification of itchgrass by morphological traits is related to the analysis of the genetic relationship of itchgrass with AFLP analysis, that allowing the assessment of the bio-diversity of itchgrass and their allelopathic potentials.